Pengaruh Kualitas Produk, Harga Dan Citra Merek Terhadap Keputusan Pembelian Brand Thanksinsomnia (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Unisma Malang Angkatan 2018) - Achmad Febryanto Irmansyah; Muhammad Ridwan Basalamah; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study means to decide and investigate the impact of item quality, cost, and brand picture on buying choices for the Thanksgiving brand. This kind of examination utilizes expalanatory research, with an example of 95 respondents. The investigation procedure utilizes numerous straight relapse examination. The reliant variable in this study is Buy Choice, while the free factors are Item Quality, Cost, and Brand Picture. The consequences of the review inferred that the factors of item quality, cost, and brand picture had a huge synchronous and halfway impact on buying choices. Keywords: Quality Product, Price, And Brand Image.